(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Body shaming has grown in popularity and is a problem that many young adults deal with on a daily basis. People fail to recognize that body shaming is a major challenge that no one is talking about and that it may have an impact on the mental health of the victim. The results showed that variables, body shame with a general weighted average of 2.94, interpreted as often; body dissatisfaction with a general weighted average of 1.6, interpreted as never; body image with a general weighted average of 1.63, interpreted as strongly disagree, body dissatisfaction with the general weighted average of 1.6 interpreted as never, self-esteem and self-worth (positive) with the general weighted average of 1.66 interpreted as strongly disagree, self-esteem and self-worth (negative) with the general weighted average of 1.73 interpreted as strongly disagree, and personal values with the general weighted average of 1.56 interpreted as strongly disagree. Using the T-Test Two-Sample Assuming Equal Variances was performed to calculate the impacts of body shaming on the development of personal values and self-worth according to the following variables. The test findings have a P -value of 0.00872136290930584, which is less than our alpha level of significance (P< 0.05), showing that there is a significant difference resulting in rejecting the Ho. The researchers of this study have four conclusions. First, the majority of the respondents in this study are mostly 21 years old, with a percentage of 31%. Second, respondents encountered few challenges in terms of body dissatisfaction, while it has been seen in the findings that most of the respondents encountered challenges in terms of body shaming. Third, it shows that body image affects the development of personal values and self-worth and that most of the respondents show a lack of confidence and love for their bodies regardless of what they wore. Lastly, the study’s overall result shows that there is a significant difference between the development of personal values and self-worth on body shaming when the respondents are grouped according to variables.